2016
DOI: 10.1155/2016/5959721
|View full text |Cite
|
Sign up to set email alerts
|

Roles of pRB in the Regulation of Nucleosome and Chromatin Structures

Abstract: Retinoblastoma protein (pRB) interacts with E2F and other protein factors to play a pivotal role in regulating the expression of target genes that induce cell cycle arrest, apoptosis, and differentiation. pRB controls the local promoter activity and has the ability to change the structure of nucleosomes and/or chromosomes via histone modification, epigenetic changes, chromatin remodeling, and chromosome organization. Functional inactivation of pRB perturbs these cellular events and causes dysregulated cell gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 128 publications
1
25
0
1
Order By: Relevance
“…Passage of the restriction point requires activation of E2F-DP, which transcribes many cell cycle genes [58][59][60][61][62][63]. Rb binding to the E2F-DP heterodimer is known to convert E2F-DP from a potent transcription activator to a potent transcription repressor [64][65][66]. Only hypophosphorylated Rb binds to the E2F-DP heterodimer [67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Passage of the restriction point requires activation of E2F-DP, which transcribes many cell cycle genes [58][59][60][61][62][63]. Rb binding to the E2F-DP heterodimer is known to convert E2F-DP from a potent transcription activator to a potent transcription repressor [64][65][66]. Only hypophosphorylated Rb binds to the E2F-DP heterodimer [67][68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, its dysregulation is directly linked to uncontrolled cell growth and carcinogenesis. 61 de Oliveira et al 62 evaluated the expression of p53 and pRb in oral malignant and premalignant lesions. They showed that compared with premalignant lesions, OSCC presented higher expression of the pRb, whereas the former presented higher expression of p53 compared with OSCC lesions.…”
Section: Cell Cycle Proliferation and Apoptosis-related Moleculesmentioning
confidence: 99%
“…More than 1000 cell cycle-dependent genes have been identified in genome-wide screens (Whitfield et al 2002, Bar-Joseph et al 2008, Sadasivam et al 2012, Grant et al 2013, Peña-Diaz et al 2013, Macosko et al 2015, Dominguez et al 2016, Fischer et al 2016a, Liu et al 2017, and expression of most of these is nearly absent in G0 cells. For the most part, expression of cell cycle-dependent genes is regulated by the RB (retinoblastoma) pocket protein family (van den Heuvel and Dyson 2008), the E2F (adenovirus early gene 2 binding factor) transcription factor family (Rowland andBernards 2006, Chen et al 2009), and MuvB (multi-vulva class B) complexes (Sadasivam and DeCaprio 2013). In recent years, it has become evident that distinct combinations of these transcription factors promote the expression of the two major classes of cell cycle genes that show peak expression either in G1/S or in G2/M.…”
Section: Introductionmentioning
confidence: 99%